Genetic characterization of slipper-shaped oyster, Crassostrea iredalei (Faustino 1932) population from Pan-ay, Capiz using Microsatellite markers a preliminary - Tatud, Christine Marie G.; Geduspan, Jane S. (2016.)
The slipper-shaped oyster, Crassostrea iredalei is economically important. Capiz, being the seafood capital of the Philippines, was also indentified as one of the major places as oyster sources. Due to the high value and demand, methods to improve production must be developed. One way is the development of selective breeding programs, which cannot be pursued without information on the genetic profile of the population. Microsatellites are the most commonly used markers in aquaculture applications. This study aimed to optimize PCR protocol for microsatellite markers (CI. F03, CI. B07 and CI. A11) to be used for characterization of Crassostrea iredalei population form Pan-ay, Capiz; and to assess the potential of these primers as molecular markers to profile oyster populations. For CI. F03, optimum temperature was at 56.1°C with polymorphic loci with 3-6 allelles per locus. For CI. B07, the optimum annealing temperature was 51.9°C which showed two distinct bands at 148.6 and 132.2 bp sizes after a gradient PCR. When five different individuals were run using the same cycling conditions, all showed the same bands at around the same sizes. For CI. A11, on the other hand, the optimum annealing temperature was also at 51.9°C of size 755.5 bp and 432.8 bp size. However, the same cycling conditions resulted to different microsatellite sizes in the five different individuals. This shows that there is variation within a population. Primer sets must be subjected to amplification using more DNA for better identification of alleles present in the population.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Oyster, Slipper-shaped (Crassostrea iredalei)